To expand \( \ln\left(\frac{1}{3} x^2\right) \) using the Quotient Rule, Product Rule, and Power Rule of logarithms, we'll proceed as follows:
-
Quotient Rule: The Quotient Rule of logarithms states that \( \ln\left(\frac{a}{b}\right) = \ln(a) - \ln(b) \). For \( \ln\left(\frac{1}{3} x^2\right) \), we can separate it into \( \ln\left(\frac{1}{3}\right) + \ln(x^2) \).
Thus: \[ \ln\left(\frac{1}{3} x^2\right) = \ln\left(\frac{1}{3}\right) + \ln(x^2) \]
-
Expanding \( \ln\left(\frac{1}{3}\right) \): Using the property that \( \ln\left(\frac{1}{3}\right) = \ln(1) - \ln(3) \), and knowing that \( \ln(1) = 0 \), we have: \[ \ln\left(\frac{1}{3}\right) = 0 - \ln(3) = -\ln(3) \]
-
Power Rule: The Power Rule of logarithms states that \( \ln(a^b) = b \ln(a) \). Therefore, \( \ln(x^2) \) can be simplified as: \[ \ln(x^2) = 2 \ln(x) \]
-
Combining everything: Now we can combine all parts together: \[ \ln\left(\frac{1}{3} x^2\right) = -\ln(3) + 2\ln(x) \]
So, the fully expanded form of \( \ln\left(\frac{1}{3} x^2\right) \) is: \[ -\ln(3) + 2\ln(x) \]
Thus, the correct choice from the responses provided is:
−ln3−2lnx (negative l n 3 minus 2 l n x).